1992
DOI: 10.1128/aem.58.6.1992-1995.1992
|View full text |Cite
|
Sign up to set email alerts
|

Growth phase, cellular hydrophobicity, and adhesion in vitro of lactobacilli colonizing the keratinizing gastric epithelium in the mouse

Abstract: Lactobacillus strains of numerous species isolated from several animal sources exhibited cellular hydrophobicities that differed from those expected on the basis of their abilities to colonize the keratinizing stratified squamous epithelium in the mouse stomach. Cells ofLactobacilusfermentum 100-33, grown to either exponential or stationary phase, were strongly hydrophilic. By contrast, cells of L. fermentum RI and six transformant derivatives of strain RI and 100-33, strains DM101 through DM106, were hydropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 14 publications
(20 reference statements)
1
20
0
4
Order By: Relevance
“…Similar results have been described by Wu et al (2012), who indicated that alteration in membrane fluidity, FA distribution, and cell integrity are common mechanisms used by L. casei to withstand severe acidification and to reduce the deleterious effect of lactic acid on the cell membrane. Other studies have made similar observations on some strains of lactobacilli (Savage, 1992;Schillinger et al, 2005), as they did not find any correlation between hydrophobicity surface and adhesion capacity of some lactobacilli to mucus and epithelial cells. Schillinger et al (2005) conducted a study on a set of Lactobacillus acidophilus strains and L. casei and reported that strains with strong surface hydrophobicity generally exhibit a significant adhesion Figure 1.…”
Section: Discussionsupporting
confidence: 53%
“…Similar results have been described by Wu et al (2012), who indicated that alteration in membrane fluidity, FA distribution, and cell integrity are common mechanisms used by L. casei to withstand severe acidification and to reduce the deleterious effect of lactic acid on the cell membrane. Other studies have made similar observations on some strains of lactobacilli (Savage, 1992;Schillinger et al, 2005), as they did not find any correlation between hydrophobicity surface and adhesion capacity of some lactobacilli to mucus and epithelial cells. Schillinger et al (2005) conducted a study on a set of Lactobacillus acidophilus strains and L. casei and reported that strains with strong surface hydrophobicity generally exhibit a significant adhesion Figure 1.…”
Section: Discussionsupporting
confidence: 53%
“…The correlation between hydrophobicity and adhesion has been debated earlier. Despite some reports (Wadström et al 1987;Ellepola and Samaranayake 2001), hydrophobicity does not appear to be a reliable indicator for adhesion (Savage 1992;Ouwehand et al 1999). Only P. freudenreichii ssp.…”
Section: Discussionmentioning
confidence: 89%
“…acidic mucopolysaccharide Fuller 1979, proteins (Conway andKjelleberg 1989) and lipoteichoic acid (Sherman and Savage 1986). In addition, Savage (1992) hypothesized that lactobacilli colonizing the keratinized stratified squamous epithelium in the murine stomach, have both hydrophilic and hydrophobic domains on their surfaces suggesting that, depending on the bacterial strains and the physical nature of the surface involved, LTA, proteins and even polysaccharides could be involved in the binding. Henriksson and Conway (1992) identified saccharide and protein moieties of Luct.…”
Section: Discussionmentioning
confidence: 99%